2018
DOI: 10.1002/chir.23036
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic alkylation of carbohydrate‐containing aldehydes with dihydroquinoline N,O‐acetals: Absolute configuration of 1,2‐dihydroquinolines

Abstract: The direct catalytic α‐amidoalkylation of dihydroquinolines with aldehydes bearing oxygen functionalities at different positions in a Mannich‐type reaction has been studied. β‐Alkoxy‐aldehyde 1d gave high enantioselectivity, albeit with an inherently poor diastereoselectivity, while the use of α‐alkoxy aldehydes 1c was detrimental also to enantioselectivity. Mannich‐type reactions have been studied for the first time using new chiral carbohydrate‐derived aldehydes 1a,b showing a reactivity markedly influenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Using a combined experimental and computational procedure, the ECD spectra of 2c-syn and 2c-anti were recorded in acetonitrile and compared with those calculated by density functional theory (DFT) on a truncated model of 2c (benzyl of Cbz replaced by methyl). 26,27 As SCHEME 2 Stereochemical models for main facial selectivity observed FIGURE 3 Transition states leading to (R,R) and (S,S)-anti diastereoisomers recently observed for other 1,2-dihydroquinoline derivatives, 28 the ECD spectra of 2c is dominated by the configuration of the endocyclic stereocentre. The configuration of the endocyclic stereocentre depends on the attack of the dienamine with either Re or Si face of the N-acyl quinolinium ion (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Using a combined experimental and computational procedure, the ECD spectra of 2c-syn and 2c-anti were recorded in acetonitrile and compared with those calculated by density functional theory (DFT) on a truncated model of 2c (benzyl of Cbz replaced by methyl). 26,27 As SCHEME 2 Stereochemical models for main facial selectivity observed FIGURE 3 Transition states leading to (R,R) and (S,S)-anti diastereoisomers recently observed for other 1,2-dihydroquinoline derivatives, 28 the ECD spectra of 2c is dominated by the configuration of the endocyclic stereocentre. The configuration of the endocyclic stereocentre depends on the attack of the dienamine with either Re or Si face of the N-acyl quinolinium ion (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Menichetti et al reported the organocatalytic asymmetric amidoalkylation of C-2 in dihydroquinolines (113), as shown in Scheme 21. [60] They used the organocatalyst 115 under In(OTf) 3 promotion to form an intermediate N-acylquinolinium ion, capable of undergoing the subsequent nucleophilic addition of the carbohydrate aldehyde 114. Subsequent reduction of the unstable aldehyde provide the diasteroisomeric mixture 116-117.…”
Section: Glycosyl Moieties Attached To C-2mentioning
confidence: 99%